Membentuk Kebiasaan Masyarakat Dalam Pengelolaan Lingkungan Melalui Digitalisasi Sampah Di Desa Wonorejo, Tutur, Pasuruan - Desy Cahyaning Utami; Muh aniar hari Swasono (Empowerment: Jurnal Pengabdian Masyarakat, 2022)
The existence of waste is a challenge for the people of Wonosari Village. This is due to low public perception and knowledge, limited facilities, and government policy support in the waste management system. Therefore, it is necessary to have a commitment in waste management so that it does not cause environmental problems. Based on Law Number 18 of 2008, waste is the remains of human daily activities and/or natural processes in solid form. In general, waste is divided into three, namely organic/wet waste, inorganic/dry waste, and hazardous waste. The purpose of this Community Service is to improve the skills of students and the community to utilize, maintain and preserve the environment through waste bank management and build networks between students and the community to use waste banks into economic goods that can improve the economy. This service method refers to the Participatory Rural Appraisal (PRA) method, which is an approach and method that allows the community to jointly analyze life problems in order to formulate real plans and policies. The results of this service are 86% of the public are aware of sorting waste, and 80% of community skills are improved through training. The potential for program sustainability where the community can sort waste properly in order to facilitate the processing process, it is necessary to mobilize waste cadres in the community to understand waste grouping and make people aware of waste care.